2019
DOI: 10.1002/mrm.28041
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional quantitative MRI of aerosolized gadolinium‐based nanoparticles and contrast agents in isolated ventilated porcine lungs

Abstract: PurposeThe objective of this study is to evaluate the suitability and performance of ultra‐short echo time (UTE) sequences for imaging and quantifying the deposition of nebulized MRI contrast agents in human‐sized lungs.MethodsNebulization of clinically used contrast agent or gadolinium‐based nanoparticles were performed using a commercial jet nebulizer in isolated and ventilated porcine lungs connected to a 3D‐printed human upper airways replica. MR images of isolated lungs were acquired on a 3T clinical MR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…To reach this objective, innovative ex vivo respiratory models appear to be an interesting preclinical tool to assess aerosol regional deposition of nano-delivery systems in healthy and pathological-like respiratory tracts [165,201]. Composed of a 3D-printed Ear-Nose-Throat replica connected to ex vivo animal respiratory tract in a hypobaric chamber simulating passive ventilation, these models appear as an innovative and promising way to quantitatively assess aerosol deposition into the lungs and to transpose it more easily to human [202,203].…”
Section: Beyond In Vivo Animal Experiments the Need To Develop Innova...mentioning
confidence: 99%
“…To reach this objective, innovative ex vivo respiratory models appear to be an interesting preclinical tool to assess aerosol regional deposition of nano-delivery systems in healthy and pathological-like respiratory tracts [165,201]. Composed of a 3D-printed Ear-Nose-Throat replica connected to ex vivo animal respiratory tract in a hypobaric chamber simulating passive ventilation, these models appear as an innovative and promising way to quantitatively assess aerosol deposition into the lungs and to transpose it more easily to human [202,203].…”
Section: Beyond In Vivo Animal Experiments the Need To Develop Innova...mentioning
confidence: 99%
“…24,26 Composed a 3D-printed Ear-Nose-Throat (ENT) replica connected to a porcine respiratory tract (RT) in a sealed enclosure simulating passive ventilation, these models proved to be an innovative way to quantitatively assess aerosol deposition into the respiratory tract. 30,51 Hence, it could be easier to assess aerosol deposition into the lungs and then to transpose it to human.…”
Section: Discussionmentioning
confidence: 99%
“…The model was set in supine position with following breathing pattern: 15 cycles per minutes, tidal volume about 500 mL and dynamic compliance about 90 cmH 2 O/mL as previously described. 26,30 A scheme of the model and complete description are provided in Supplementary Information.…”
Section: Ex Vivo Respiratory Model For Preclinical Aerosol Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vivo study of localized AGuIX ® intrathecal instillation in mice showed increased tumor targeting and radiotherapy efficiency compared to systemic injection [12,18,19]. As well, AGuIX ® aerosolization may represent a promising theranostic approach for the treatment of lung tumors and metastases [22]. In order to mimic NP's liquid aerosolization, we used two innovative 3D human models of the respiratory tract, one without tumor cells (MucilAir ™ /Epithelix) and one with A549 adenocarcinoma nodules (OncoCilAir ™ /Oncotheis) [23].…”
Section: Introductionmentioning
confidence: 99%